Źle przemieszani - Czapliński, Przemysław (Poznańskie Studia Polonistyczne. Seria Literacka, 2013)
The main statement of the article is that Polish-Jewish and Jewish-Polish biographies have an ambiguous ontological status. The status, which the article describes as spectral, is traced in Polish literature over the last twenty four years (from mid-80s till now). Three conventions have been identified, which, because of their openness to ontologically incomplete beings, are good expressions of complications of biography and identity. The conventions are romance, genealogy, and horror. The writers who use these conventions aim at representing a concrete Polish-Jewish or Jewish-Polish biography, but the phantasmatic quality of combination of what is Polish with what is Jewish leads to unreality of all elements of a novel. Consequently, not only Jewish characters and Jewish identity, but also Poles and Polish identity become phantasmatic.